Prenatal diagnosis of 18p deletion and 8p trisomy syndrome: literature review and report of a novel case - Maria Papamichail; Anna Eleftheriades; Emmanouil Manolakos; Adamantia Papamichail; Panagiotis Christopoulos; Gwendolin Manegold-Brauer; Makarios Eleftheriades (BMC, 2024)
Abstract 18p deletion syndrome constitutes one of the most frequent autosomal terminal deletion syndromes, affecting one in 50,000 live births. The syndrome has un-specific clinical features which vary significantly between patients and may overlap with other genetic conditions. Its prenatal description is extremely rare as the fetal phenotype is often not present during pregnancy. Trisomy 8p Syndrome is characterized by heterogenous phenotype, with the most frequent components to be cardiac malformation, developmental and intellectual delay. Its prenatal diagnosis is very rare due to the unspecific sonographic features of the affected fetuses. We present a very rare case of a fetus with multiple anomalies diagnosed during the second trimester whose genomic analysis revealed a 18p Deletion and 8p trisomy Syndrome. This is the first case where this combination of DNA mutations has been described prenatally and the second case in general. The presentation of this case, as well as the detailed review of all described cases, aim to expand the existing knowledge regarding this rare condition facilitating its diagnosis in the future.